The Income and Price Elasticities of Tourist Demand in Thailand - MALLIGA, Sompholkrang (Journal of Environmental Management and Tourism, 2016)
The objectives of this study are to estimate the income and price elasticities of tourist demand in Thailand. A linear expenditure system is employed in this paper. It is assumed that a consumer maximizes his or her utility subject to a budget constraint. A data set of consumer price indices (CPI) of six commodities and the expenditure of tourists from selected countries for 1985 – 2012 are used. This paper focuses on the expenditure of tourists from Thailand’s major tourism markets including Laos People’s Democratic Republic, the People’s Republic of China, Malaysia, Japan, Korea, the Russian Federation, India, Australia, the United Kingdom and the United States of America. The data are obtained from the Tourism Authority of Thailand, the Department of Tourism, the Ministry of Commerce, and the National Statistical Office. It is revealed that the income and prices of six commodities affect the expenditure of tourists from various countries differently. International tourists from different countries have different preferences for commodities. Pricing strategy may respond to the low price elasticity and may increase the tourism revenues of inbound tourism in Thailand. The study provides some interesting findings that may help to provide a better understanding of the behavior of international tourists.
Keywords: tourist demand; income elasticity; price elasticity; linear expenditure system